Identifying the Fetal Heart Rate and gender with Intuitionistic Fuzzy Total edge Magic Labelling - Aruchamy, Pradeepa; Mahagaonkar, Pralahad; Ganesan, Gomathi; Dhandapani, Prasantha Bharathi; Yahya, Nisky Imansyah (Jambura Journal of Biomathematics (JJBM), 2025)
The application of Intuitionistic fuzzy total edge magic labelling to a graphical image at the 20th week of gestation provides insights into facilitates gender prediction as well as assessment of fetal blood flow on a second-trimester Doppler ultrasound screen. Ultrasounds screen the fetal heart rate during the 20th week of gestation using Doppler ultrasound for blood flow. A fetal heart rate above 2.5 beats per second suggests a female baby, while a rate less than 2.5 beats per second indicates a male baby. We convert the fetal heart blood flow into a graphical image and label it using intuitionistic fuzzy total edge magic labelling.